A SEMIOATIC ANALYSIS OF “CITRA” PRODUCT OF SKIN CARE ADVERTISEMENT - Suswanto Ismadi Megah S. (Universitas Riau Kepulauan, 2015)
This study is about advertiemnet of the skin care for women, particularly in Indoensia. This study used semiotic theory of the advertisement of the women product od the skin care. So, this product sold out due to of this case.This study took adat from the product of the “cira” product of the skin care. So, this study only used semiotics study of the skin care of the citra product. This study can be concluded that the skin care/treatment for women with natural ingredient. This shows that the meaning of the sign of the women is skin. The skin is as measurement of the women performance and esteem. Keywords : Semiotics, Product and Advertisement